Controlled synthesis of carbon nanonetwork wrapped graphite felt electrodes for high-performance vanadium redox flow battery. (1st November 2022) - Lv, Yanrong; Yang, Yujie; Gao, Jiayi; Li, Jin; Zhu, Wenjie; Dai, Lei; Liu, Yongguang; Wang, Ling; He, Zhangxing
Highlights: Nanonetwork wrapped graphite felt is prepared by in situ electrodeposition. A VRFB dual-function electrode wrapped with carbon nano-network is prepared. There is excellent connectivity between wrapped nano-network and graphite felt. Binder-free nano-network enables graphite felt show excellent cycling stability. Abstract: In this work, nitrogen-doped carbon nanonetwork wrapped dual-function electrode is fabricated in-situ by a simple electrodeposition method. By changing the electrodeposition time and calcination temperature, the morphology of carbon nanonetwork and the presence of nitrogen on graphite felt are controlled. The in-situ wrapped nanonetwork can increase the specific surface area of graphite felt electrode, improve the connectivity between graphite felt and carbon nanonetwork, and reduce the electrode resistance. The composite electrode is prepared without the involvement of adhesive, which enables the carbon nanofibers to exist stably on the graphite felt surface during charging and discharging. At 100 mA cm –2, the energy efficiency of modified cell is 79.2%, which is 8.8% higher than that of blank cell. Using the prepared electrode, VRFB has a discharge capacity of 350 mA h at 250 mA cm –2, while the blank cell cannot work normally. This work proposes a method for preparing a high-performance, high-stability composite electrode, which enables the carbon nanonetwork stably exist on the surface of graphite felt without a binder. Graphical abstract: Image, graphical abstract